Advanced numerical analyses on thermal, chemical and dilution effects of water addition on diesel engine performance and emissions utilizing artificial inert species. (15th April 2019) - Neshat, Elaheh; Bajestani, Amirhossein V.; Honnery, Damon
Highlights: A multi zone model is applied to investigate the effect of water addition on diesel engine performance and emissions. Artificial inert species method is utilized for estimation of different effects of water addition. Thermal effect of water is greater than its dilution and thermodynamic effects. Dilution effect of water is more significant than its chemical effect. Low values of water content increase engine thermal efficiency and engine exhaust emissions. Abstract: The main purpose of current study is investigation on different effects of water addition on diesel engine performance and emissions. A thermodynamic multi-zone model and a semi-detailed chemical kinetics mechanism, including 76 species and 327 reactions, are applied for diesel combustion simulation. The combustion chamber is divided into different zones and conductive heat transfer and bulk and diffusion mass transfer sub models are considered between the zones. Convective and radiation heat transfers are considered between the in-cylinder charge and combustion chamber walls. First, the accuracy of the model was estimated for three different operating modes, and then six different amounts of water were added to the fuel and its effects on diesel combustion were investigated. Chemical, dilution and thermal effects of water are studied using artificial inert species. The results show that the premixed combustion timing was advanced by water addition. Peak values of in-cylinder pressure and heat release rate decreases by water addition. Water addition has caused the maximum amount of radicals in the combustion chamber to be reduced and the time of their formation is delayed. Water addition increases the exhaust soot and reduces exhaust NOx. Thermal effect of water on start of combustion and emissions formation is more significant than its dilution and chemical effects. Using small quantities of water will increase the thermal efficiency of the engine and reduce emissions from it.